PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS GAMES UNTUK PEMBELAJARAN MATEMATIKA DI SMP - Nuryanti Dwi Putri (Jurnal Edukasi dan Penelitian Matematika, 2018)
Multimedia interactive is one of the important thing on mathematics learning to increase effectiveness and efficiency. However multimedia which used in school was not interactive and motivate. So, it was developed interactive learning multimedia based on games on set material. Aim of this research was to result the valid, practice, and effective multimedia. Research was a design research using Plomp model were devided into three stages namely preliminary research, prototyping, and assessment phase. Data was got by questionnaires, validation and interview sheets were analyzed using technique of descriptive quantitative and result of test was analyzed using Sukmadinata formula. Result shows that quality of multimedia are very valid with characteristic content as according to state of the art knowledge, construct has multimedia component, language appropriate to EBI, and visuals are technically good; very practical from ease of using, time of using and the interest of student; and effective for improving students understanding and motivation.Keywords – interactive multimedia, games, design research.